Examining Comprehension Strategy Instruction With English Learners' Problem Solving: Study Findings and Educator Preparation Implications. (August 2018) - Orosco, Michael J.; Abdulrahim, Naheed A.
Educator preparation in comprehension strategy instruction (CSI) is essential to meeting the needs of English learners (ELs) in contemporary schools. This article provides teacher educators and professional developers with concrete examples of practices to prepare classroom teachers in comprehensive strategy instruction, based on an experimental study that examined the effect (.37) of CSI on third-grade students' ( n = 78) word-problem-solving (WPS) performance. CSI included problem-solving strategies that (a) helped students to understand the relevant and irrelevant information in a word problem's question; (b) helped students to restate the problem orally, which allowed them to understand, to construct meaning, and to clarify any misunderstanding about the question; and (c) provided instructional feedback with student collaboration for problem solving and solution. Findings indicate that a focus on CSI may help facilitate WPS skills developing for ELs at risk of mathematics-learning difficulties (MLD). Educator preparation recommendations are embedded throughout with implications for future research and practice also discussed.